Phylogenetic evidence from freshwater crayfishes that cave adaptation is not an evolutionary dead‐end. (20th September 2017) - Stern, David B.; Breinholt, Jesse; Pedraza‐Lara, Carlos; López‐Mejía, Marilú; Owen, Christopher L.; Bracken‐Grissom, Heather; Fetzner, James W.; Crandall, Keith A.
Abstract: Caves are perceived as isolated, extreme habitats with a uniquely specialized biota, which long ago led to the idea that caves are "evolutionary dead‐ends." This implies that cave‐adapted taxa may be doomed for extinction before they can diversify or transition to a more stable state. However, this hypothesis has not been explicitly tested in a phylogenetic framework with multiple independently evolved cave‐dwelling groups. Here, we use the freshwater crayfish, a group with dozens of cave‐dwelling species in multiple lineages, as a system to test this hypothesis. We consider historical patterns of lineage diversification and habitat transition as well as current patterns of geographic range size. We find that while cave‐dwelling lineages have small relative range sizes and rarely transition back to the surface, they exhibit remarkably similar diversification patterns to those of other habitat types and appear to be able to maintain a diversity of lineages through time. This suggests that cave adaptation is not a "dead‐end" for freshwater crayfish, which has positive implications for our understanding of biodiversity and conservation in cave habitats.